Polarized Neutron Diffraction as a Tool for Mapping Molecular Magnetic Anisotropy: Local Susceptibility Tensors in CoII Complexes. Issue 2 (3rd December 2015) - Ridier, Karl; Gillon, Béatrice; Gukasov, Arsen; Chaboussant, Grégory; Cousson, Alain; Luneau, Dominique; Borta, Ana; Jacquot, Jean‐François; Checa, Ruben; Chiba, Yukako; Sakiyama, Hiroshi; Mikuriya, Masahiro
Abstract: Polarized neutron diffraction (PND) experiments were carried out at low temperature to characterize with high precision the local magnetic anisotropy in two paramagnetic high‐spin cobalt(II) complexes, namely [Co II (dmf)6 ](BPh4 )2 (1 ) and [Co II 2 (sym‐hmp)2 ](BPh4 )2 (2 ), in which dmf= N, N ‐dimethylformamide; sym‐hmp=2, 6‐bis[(2‐hydroxyethyl)methylaminomethyl]‐4‐methylphenolate, and BPh4 − =tetraphenylborate. This allowed a unique and direct determination of the local magnetic susceptibility tensor on each individual Co II site. In compound1, this approach reveals the correlation between the single‐ion easy magnetization direction and a trigonal elongation axis of the Co II coordination octahedron. In exchange‐coupled dimer2, the determination of the individual Co II magnetic susceptibility tensors provides a clear outlook of how the local magnetic properties on both Co II sites deviate from the single‐ion behavior because of antiferromagnetic exchange coupling. Abstract : All mapped out : Polarized neutron diffraction on a paramagnetic single crystal permits mapping of the molecular magnetic anisotropy regardless of the number of molecular orientations in the crystal cell and the investigation of the competing roles of magnetic exchange and single‐ion anisotropy in polynuclear complexes.